Detection of Molecular Clouds in the PeVatron Candidate Source LHAASO J0341+5258 by the Nobeyama 45-m Radio Telescope - Tsuji, Naomi; Takekawa, Shunya; Mori, Kaya; Mitchell, Alison; Zhang, Shuo; Bangale, Priyadarshini; DiKerby, Stephen; Ergin, Tülün; Woo, Jooyun; Safi-Harb, Samar; Kasuya, Shinta (Astrophysical Journal, 2025)
We report a new CO observation survey of LHAASO J0341+5258, using the Nobeyama Radio Observatory 45-m telescope. LHAASO J0341+5258 is one of the unidentified ultra-high-energy (UHE; E > 100 TeV) gamma-ray sources detected by LHAASO. Our CO observations were conducted in 2024 February and March, with a total observation time of 36 hr, covering the LHAASO source (∼0 . ° 3-0 . ° 5 in radius) and its surrounding area (1° × 1 . ° 5). Within the LHAASO source extent, we identified five compact (<2 pc) molecular clouds at nearby distances (<1-4 kpc). These clouds can serve as proton-proton collision targets, producing hadronic gamma rays via neutral pion decays. Based on the hydrogen densities (700-5000 cm−3) estimated from our CO observations and archived H i data from the Dominion Radio Astrophysical Observatory survey, we derive the total proton energy of Wp (E > 1 TeV) ∼ 1045 erg to account for the gamma-ray flux. One of the molecular clouds appears to be likely associated with an asymptotic giant branch (AGB) star with an extended CO tail, which may indicate some particle acceleration activities. However, the estimated maximum particle energy below 100 TeV makes the AGB-like star unlikely to be a PeVatron site. We conclude that the UHE emission observed in LHAASO J0341+5258 could be due to hadronic interactions between the newly discovered molecular clouds and TeV-PeV protons originating from a distant SNR or due to leptonic emission from a pulsar wind nebula candidate, which is reported in our companion X-ray observation paper.
CRIS-Team Scopus Importer:2025-04-18